Feminist Transgressions and Critical Dys-u-topian Drama: Ann Jellicoe, Bryony Lavery and Germaine Greer - Lorek-Jezińska, Edyta (Zagadnienia Rodzajów Literackich, 2020)
Referring to the discussion on the critical potential of dystopias in fiction, the article examines twentieth century feminist plays by Ann Jellicoe, Bryony Lavery and Germaine Greer for their presentation and critical deconstruction of gender roles, social structures and power relations. In the plays discussed in the article the critical and transgressive strategies used by the playwrights question the possibility of separating utopias and dystopias, showing how they are linked to and dependent on each other. Refusing to provide neat endings and definitions, the plays open up to contradictory readings by mixing the elements of dystopia and utopia and inviting critical and self-reflexive interpretations directing the critique of the past and the future towards the present.